Introductory Remarks on Ideology and Sociology - Franco Ferrarotti (Academicus, 2021)
The main contention of this paper is that the eventual decline of ideology would pave the way to personalism and piece-meal policy-making. In this respect, sociology should analyze the process of social evolution while the ideological goals tend to concentrate on the middle-range and distant future.